MODERASI VARIABEL KEBIJAKAN DIVIDEN PADA PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - I GUSTI AGUNG DIDIT EKA PERMADI (GANEC SWARA, 2021)
The research aims at analyzing the effects of liquidity, leverage, and profitability towards company value, analyzing the potency of dividend policy in moderating the effects of liquidity, leverage, and profitability towards company value. This research is causal research. The sample was selected by using purposive sampling technique. The data gathering implemented in this research was documentation technique. The entire data source in this research was secondary data in a form of ICMD (Indonesian Capital Market Directory). The analysis tools used in this research was Moderated Regression Analysis (MRA). This research used statistics SPSS Statistics 17.0 for Windows as statistics analysis software aid. The results of the research are the liquidity did not have effects towards company value; dividend policy could not moderate the correlation between liquidity towards company value; leverage had positive effects towards company value; dividend policy could moderate the correlation between leverage towards company value; profitability had positive effects towards company value; and dividend policy could not moderate the correlation between profitability towards company value